Annulment of Lease Agreements Based on Third-Party Undue Influence under the Indonesian Civil Code - Nadine Adika Tifana; Etty Haryati Djukardi; Sherly Ayuna Putri (JUSTISI, 2025)
This study aims to examine the evidentiary process in lease agreement disputes involving undue influence and to analyze the legal protection afforded to lessees under the Indonesian Civil Code. The research gives particular attention to cases where undue influence is not exerted by the contracting parties themselves but by third parties who intervene in the contractual relationship. This study uses a normative legal research method combining conceptual, statutory, and case analysis, complemented by an empirical component through a structured interview with a District Court judge experienced in lease disputes. Decision No. 8/Pdt.G/2022/PN Mdn was purposively selected as the case study because it directly involves annulment of a lease agreement based on third-party undue influence. The novelty of this study lies in its systematic analysis of undue influence exerted by third parties in lease agreements, an aspect rarely examined in Indonesian legal doctrine and not explicitly regulated under positive law. This contribution fills an academic gap while providing a legal-argumentative framework that integrates doctrinal analysis with judicial practice. The results of this study indicate that third-party undue influence introduces an additional evidentiary burden: claimants must prove the lessee’s vulnerable condition, the deliberate intervention of a third party, and a causal link between that intervention and the lessee’s consent. Furthermore, legal protection for good-faith lessees is reinforced by Civil Code provisions, including Articles 1315, 1320–1321, 1338(3), and 1365, as well as supporting jurisprudence that emphasizes fairness and proportionality in assigning liability. This study concludes that undue influence by a third party can constitute a valid legal ground for annulment of lease agreements and that lessees acting in good faith must be shielded from disproportionate liability. The findings reinforce the judiciary’s duty to uphold substantive justice and provide guidance for courts, policymakers, and contracting parties in safeguarding fairness within Indonesian contract law.